2017
DOI: 10.1007/s11274-017-2383-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, purification and characterization of novel Cu-containing nitrite reductase from the Bacillus firmus GY-49

Abstract: Nitrite is generated from the nitrogen cycle and its accumulation is harmful to environment and it can be reduced to nitric oxid by nitrite reductase. A novel gene from Bacillus firmus GY-49 is identified as a nirK gene encoding Cu-containing nitrite reductase by genome sequence. The full-length protein included a putative signal peptide of 26 amino acids and shown 72.73% similarity with other Cu-containing nitrite reductase whose function was verified. The 993-bp fragment encoding the mature peptide of NirK w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…are rarely reported. Gao, et al [40] reported molecular and structural analyses of Cu-NIR in gram-positive bacteria of Bacillus firmus GY-49. The present study provides further evidence for the existence of nirK in Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…are rarely reported. Gao, et al [40] reported molecular and structural analyses of Cu-NIR in gram-positive bacteria of Bacillus firmus GY-49. The present study provides further evidence for the existence of nirK in Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accumulation of nitrite nitrogen was lower than that in the control treatment in the presence of 0.05 mg Cu 2+ L −1 . A Cu-containing nitrite reductase encoded by the nirK gene has been confirmed to be the key enzyme in the denitrification pathway, and the addition of Cu 2+ could increase the nitrite reductase (NiR) activity, which would result in less nitrite accumulation and improved denitrification efficiency [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…14 The reaction was carried out in a 0.5 mL closed vial containing 100 mM potassium phosphate buffer (pH 6.5), 50 mM methyl viologen and 2.5 M sodium nitrite, 1 M sodium chloride and 0.02 mL puried enzyme. 14 The reaction was initiated with the addition of 50 mL sodium dithionite (1 M) and the vial gently swirled. Aer incubation at 37 C for 10 min, the reaction was terminated by vigorous shaking for 3 min.…”
Section: In Vitro Analytical Methods For Detecting the Enzyme Activitymentioning
confidence: 99%
“…The heterogenous expression of recombinant LJ01-NIR in E. coli were puried by Ni 2+ -NTA affinity chromatography (GE, USA) and Superdex 200 gel ltration chromatography (GE, USA) using a fast protein liquid chromatography system (AKTA Purier Explorer, Pharmacia, Uppsala, Sweden), referring to Gao's method with slight modication. 14…”
Section: In Vitro Analytical Methods For Detecting the Enzyme Activitymentioning
confidence: 99%